A Low-loss Wideband Filtering Coupler with Patterned Substrate Integrated Suspended Line (SISL) Technology - Li Ma; Yongle Wu; Mingxing Li; Weimin Wang; Yuanan Liu (Applied Computational Electromagnetics Society Journal (ACES), 2019)
A wideband filter-integrated coupler has been presented using the substrate integrated suspended line structure with patterned substrate. This coupler is composed of a two-line coupled line, two variant coupled lines, and four three-line coupled lines at each port. The SISL structure is composed of five print circuit boards, connected together by metal via holes. There is a hollowed substrate between two air cavities to reduce the loss. For further explanation, two wideband filtering SISL couplers operating at different operating frequencies with equal/unequal power divisions are designed and simulated, of which a specific coupler working at 1.66 GHz with a relative bandwidth of about 52.56% is fabricated and measured. The experimental results agree well with the theoretical and simulation ones. This proposed coupler has many advantages such as selfpackaged, low loss, filter integration, arbitrary power division ratio, and inherent DC-block function.